"HOW TO MARKET THE PRESSAC BRAND TO EXISTING AND POTENTIAL CUSTOMERS" - HASSAN, Ali Murtaza (2012)
PRESSAC COMMUNICATIONS LTD, a privately owned UK based company specializing in the design and manufacturing of mechanical and electronic products is suffering from a weak brand image. The purpose of this research is to scan PRESSAC’s internal and external environment in order to develop a better understanding of where PRESSAC stands, and attempt to identify opportunities PRESSAC can benefit from. The second major aspect of this research is to understand the positive role that business-to-business (B2B) branding and B2B relationship marketing can play for PRESSAC.